Assessment, creativity and learning: A personal perspective - Richard Hickman (Future in Educational Research)
AbstractThis paper presents a personal view (a view coloured by my cultural environment and upbringing) of young people's education. I look in particular at assessment practices and detail my understanding of the nature of learning, focusing on creativity and the tensions associated with schooling and creative behaviour. Drawing upon and developing my earlier work in the light of further research and experience, I give an overview of assessment practices and approaches to teaching and learning and argue for a learner‐centred approach with a focus on practical work and an environment that promotes creative problem‐solving across the whole curriculum. A pedagogical strategy is presented that is based on four areas of activity: reacting, researching, responding, and reflecting.